Vehicle safety inspection systems : how effective? - Crain, W. Mark. (Washington : American Enterprise Institute for Public Policy Research, 1980)
The core of this work is a statistical analysis that compares death and accident rates in states with and without inspection programs.
Includes bibliographical references.
hza 29/01/2019, rpm 19/02/2019
Loans
Keywords: Automobiles; Traffic safety